Maxillary incisor retraction: evaluation of different mechanisms - Antônio Carlos de Oliveira Ruellas; Matheus Melo Pithon; Rogério Lacerda dos Santos (Dental Press Editora, 2013)
OBJECTIVE: To mechanically evaluate different systems used for incisors retraction. METHODS: Three different methods for incisors retraction using 0.019 x 0.025-in stainless steel wire were evaluated. The samples were divided into three groups: Group A (retraction arch with 7-mm high vertical hooks); Group G3 (elastic chain attached to the miniimplant and to the 3-mm stainless steel hook soldered to the retraction arch); Group G6 (elastic chain attached to the mini-implant and to the 6-mm stainless steel hook soldered to the retraction arch). A dental mannequin was used for evaluation in order to simulate the desired movements when the device was exposed to a heat source. The analysis of variance (ANOVA) and the Tukey test were used (p < 0.05). RESULTS: The results demonstrated that Groups G3 and G6 exhibited less extrusion and less incisor inclination during the retraction phase (p < 0.05). With regard to incisor extrusion, statistically significant differences were observed between Groups A and G3, and between Groups A and G6 (p < 0.05). Regarding incisor inclination, statistically significant differences were observed between the three systems evaluated (p < 0.05). CONCLUSIONS: Arches with 6-mm vertical hooks allow the force to be applied on the center of resistance of the incisors, thus improving mechanical control when compared with the other two systems.